Optimization of Hole Variations in Honeycomb Charcoal Briquettes from Corn Waste for Enhanced Combustion Efficiency - Agustinus Agustinus; Rombe Allo; Enos Tambing; Selyus Rantepulung; Mickael Ruben Kaiway (G-Tech: Jurnal Teknologi Terapan, 2025)
This study investigates the viability of corn byproducts as an alternative energy source via conversion into honeycomb charcoal briquettes. Discarded corn byproducts are transformed into briquettes to mitigate fossil fuel reliance, particularly in the Arso region. This research aims to assess the energy output of briquettes with varying perforation configurations (4, 8, and 12 holes) and a diameter of 5 inches. The Water Boiling Test (WBT) method, utilizing temperature measurement tools such as a K-type thermocouple and an infrared thermometer, was utilized for performance assessment. One liter of water was heated to its boiling point during the experiment. The results indicated that the 8-hole briquette had the quickest boiling time of 25 minutes, with a fuel consumption rate of 2.8 × 10⁻³ kg/s. In comparison, the 4 and 12-hole briquettes required 35 minutes, with an average fuel usage of 2.86 g/s. The maximum combustion temperature for the 4-hole briquette was measured at 589°C, while the 12-hole briquette reached a mere 427°C. These outcomes demonstrate that the 8-hole briquette possesses superior efficiency. A decrease in hole quantity adversely affects boiling speed, while an increase in holes results in greater fuel consumption. These findings highlight the importance of optimized briquette design in improving biomass fuel efficiency.